2014
DOI: 10.1097/pcc.0000000000000021
|View full text |Cite
|
Sign up to set email alerts
|

Is Propofol a Friend or a Foe of the Pediatric Intensivist? Description of Propofol Use in a PICU*

Abstract: The use of propofol infusions was in concordance with PICU local practice, and propofol infusion syndrome did not developed in patients. In agreement with previous recommendations, propofol infusions in the PICU appear to be safe when limiting doses to 4 mg/kg/hr and for less than 24 hours; however, appropriate monitoring of adverse effects is still warranted due to absence of robust evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 18 publications
1
23
0
2
Order By: Relevance
“…Propofol infusions of doses greater than 4mg/kg/hr for more than 48 hours should be avoided [191, 192, 125]. However, it should be borne in mind that in critically ill children, development of PRIS has been reported even after 3–5 hours of high-dose propofol anesthesia and rates as low as 1.4 mg kg −1 h −1 [193].…”
Section: ) Propofol and Mitochondriamentioning
confidence: 99%
“…Propofol infusions of doses greater than 4mg/kg/hr for more than 48 hours should be avoided [191, 192, 125]. However, it should be borne in mind that in critically ill children, development of PRIS has been reported even after 3–5 hours of high-dose propofol anesthesia and rates as low as 1.4 mg kg −1 h −1 [193].…”
Section: ) Propofol and Mitochondriamentioning
confidence: 99%
“…The incidence of PRIS is~1 % in adult patients [40]. There are no valid data for children, but propofol use in children in pediatric intensive care units (PICUs) appeared to be safe when doses did not exceed 4 mg/kg/h and use was restricted to <24 h [41,42]. Patients should be monitored closely for the presence of elevated triglycerides and lactic acidosis [43].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Usually, aminoglycoside-induced RFS is seen in patients with impaired renal function, but some reports of patients with normal kidney function exist [143]. Gentamicin enters the cell through the megalin-cubulin system [41]. Intracellular gentamicin can decrease the function of mitochondrial ribosomes [144] and interfere with the conversion of ADP to ATP [145].…”
Section: Aminoglycosides and Tetracyclinesmentioning
confidence: 99%
“…[41][42][43] Recent studies by Koriyama et al and by Krussell et al showed that the use of continuous infusion of propofol limited to 4 mg/kg/h for less than 48 hours is safe, with no cases of propofol infusion syndrome reported in children. 44,45 Another sedative agent indicated for adult use, with benefits over benzodiazepines, is dexmedetomidine, an alfa-2 agonist with sedative and analgesic properties. Riker et al demonstrated a decrease in duration of mechanical ventilation and a reduction in the prevalence of delirium in adults, when comparing the use of dexmedetomidine to benzodiazepines.…”
Section: Resultsmentioning
confidence: 99%